Pengaruh Kindness terhadap Subjective Well-being pada Orang Tua Anak Berkebutuhan Khusus - Hakim, Sabrina; Zulfiana, Uun (Universitas Muhammadiyah Malang, 2024)
Subjective well-being plays a crucial role in helping parents of children with special needs find meaning and positivity in life. Research indicates a positive relationship between subjective well-being and kindness. This study aims to investigate the influence of kindness on the subjective well-being of parents who have children with special needs. The research employs a quantitative method with a correlational approach. Participants included 150 parents of children with special needs, selected through snowball sampling techniques. The instruments used for measurement were the Satisfaction With Life Scale (SWLS), the Positive Affect Negative Affect Scale (PANAS), and the VIA Inventory of Strengths (VIA-IS 120). Data analysis was conducted using simple regression. The results demonstrated a significant influence of kindness on the positive affect dimension (\( p < 0.001 \)). This finding suggests that as kindness increases, so does positive affect among parents of children with special needs.